Experience with joint-ventures in Yugoslavia - Peter Plötz (Intereconomics, 1975)
Yugoslavia laid the legal foundations for capital investments by foreign firms in 1967. It was the first socialist country to permit foreign investments and apart from Roumania and Hungary is still the only one which has done so. Prerequisites have thereby been provided for very close relations between enterprises belonging to different economic systems. The foreign capital participation must as a rule not exceed 49 p.c. of the total capital.
Keywords: 330; Germany